Lithium aluminosilicate reinforced with carbon nanofiber and alumina for controlled-thermal-expansion materials - Borrell, Amparo (Sci Technol Adv Mater, 2012)
Materials with a very low or tailored thermal expansion have many applications ranging from cookware to the aerospace industry. Among others, lithium aluminosilicates (LAS) are the most studied family with low and negative thermal expansion coefficients. However, LAS materials are electrical insulators and have poor mechanical properties. Nanocomposites using LAS as a matrix are promising in many applications where special properties are achieved by the addition of one or two more phases. The main scope of this work is to study the sinterability of carbon nanofiber (CNFs)/LAS and CNFs/alumina/LAS nanocomposites, and to adjust the ratio among components for obtaining a near-zero or tailored thermal expansion. Spark plasma sintering of nanocomposites, consisting of commercial CNFs and alumina powders and an ad hoc synthesized β-eucryptite phase, is proposed as a solution to improving mechanical and electrical properties compared with the LAS ceramics obtained under the same conditions. X-ray diffraction results on phase compositions and microstructure are discussed together with dilatometry data obtained in a wide temperature range (−150 to 450 °C). The use of a ceramic LAS phase makes it possible to design a nanocomposite with a very low or tailored thermal expansion coefficient and exceptional electrical and mechanical properties.